Absence of Renal Protection of an Aqueous Extract of Lemongrass (Cymbopogon citratus) Cultivated in Costa Rica, Using a Model of Acute Renal Failure in Wistar Rats - Navilla, Apú Leitón; Manuel, Fallas Ramírez Jose; Josué, Orozco Aguilar; Alexander, Rodríguez Arrieta Jesús; José, Mora Román Juan (Asian Journal of Pharmaceutical Research and Development, 2019)
citratus, known as zacate de limón (lemongrass), is commonly used in Costa Rica for the treatment of "kidney diseases." Therefore, the activity as renal protector of an aqueous extract of this plant was evaluated after oral administration, in a model of acute kidney injury (AKI) in female Wistar rats. For this, an aqueous extract was characterized by thin layer chromatography and qualitative phytochemical tests. An AKI model induced by potassium chromate in female Wistar rats was carried out. The serum concentration of creatinine, sodium, potassium and glucose were determined, as well as the concentrations of creatinine, sodium, potassium, glucose and proteins in urine, together with the urinary flow determination. A histopathological analysis of the subjects’ kidneys was performed, and the presence of kidney damage was identified. The characterization of the extract by thin layer chromatography, and ferric chloride, Shinoda and Wilson tests gave negative results for phenols, tannins and flavonoids. No positive changes were observed in renal function markers in urine. No histopathological evidence of nephroprotective activity of the aqueous extract of C. citratus was found. It is concluded that the aqueous extract of C. citratus obtained by infusion does not possess nephroprotective activity at a dose of 150 mg/kg evaluated by the AKI in female Wistar rats.